STUDY OF THE MAGNETIC FIELD OF THREE PHASE LINES OF SINGLE CORE POWER CABLES WITH TWO-END BONDING OF THEIR SHIELDS - V.Yu. Rozov (National Technical University "Kharkiv Polytechnic Institute", 2015)
The study tested the process of the magnetic field (MF) mitigation in the HV three-phase power cable lines (CL) made of single core cables in two-ends bonding of their shields. Developed the technique of numerical simulation and calculation of the MF of CL based on its axisymmetric calculation model using the finite element method that allowed to describe the condition of closing the cable shields at the both ends of the CL and solve the problem in two-dimensional formulation. The authors show the possibility of MF mitigation of the three-phase CL by increasing the cross-section of closed cable shields, which in some cases may be an alternative to external electromagnetic shields. Obtained and experimentally validated in laboratory and field conditions with an accuracy of no more than 5 % the value of mitigation coefficients of MF of three-phase three-wire CL in two-ends bonding of their shields depending on the technical parameters of the cables and the geometry of their installation, which is important for the design of new cable power lines. Their values are in the range from 0.99 to 0.32 when the cross sections of cable shields are from 25 mm2 to 200 mm2 and the distance between the axes of the cables are from 0.1 to 0.5 m. The results show the ability to execute design of cable power lines in residential areas, taking into account both the sanitary standards of the MF, as well as to energy efficiency.